Photocuring 3D printing metal slurry and preparation method thereof
By using composite powder of organic shell and metal core in photocuring 3D printed metal paste, combined with two ball mills and component optimization, the curing characteristics and stability problems are solved, and high-precision and high-performance metals are achieved Part print.
Patent Information
- Application Number
- CN202411522628.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-01-03
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing photocuring 3D printed metal pastes have poor curing characteristics and poor stability, resulting in internal defects, pores or cracks in the printing parts, affecting the quality and performance of the parts.
The composite powder containing an organic shell and a metal core is used to uniformly disperse the composite powder through two ball milling processes, adjust the viscosity and curing speed, and optimize the composition ratio to improve the stability and uniformity of the slurry.
It significantly improves the curing thickness and stability of photocured 3D printed metal paste, reduces printing defects, and ensures high precision, surface finish and good mechanical properties of the components.
Smart Images

Figure BDA0005108375190000111 
Figure HDA0005108375210000011 
Figure HDA0005108375210000012
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of metal additive manufacturing and relates to a photocurable 3D printing metal slurry and a preparation method thereof. Background Art
[0002] Additive manufacturing, as a revolutionary manufacturing technology, especially when applied to the field of metal 3D printing, has shown great potential for manufacturing complex and high-precision metal structures. However, the mainstream metal additive manufacturing technology, powder bed fusion, limits the range of printable metals due to its process of completely melting the powder and is accompanied by defects caused by high thermal gradients and thermal stress. Although photocuring 3D printing can avoid directly melting metal and efficiently manufacture parts with fine features and overhanging structures at room temperature, this technology still faces many challenges in practical applications, the most notable of which is the large difference in refractive index between metal powder and polymer matrix and the easy sedimentation of metal powder, which makes it difficult to prepare a stable slurry with good photocuring properties and cannot meet the needs of photocuring 3D printing metal. First, due to its high refractive index characteristics, the penetration distance of light in the photocuring slurry formed by mixing with the polymer matrix is severely limited. This refractive index mismatch leads to uneven propagation and energy distribution of the laser or light source in the slurry, which in turn affects the efficiency and uniformity of photocuring. The inadequacy of photocuring properties not only reduces manufacturing efficiency, but may also cause internal defects in the printed parts, such as incompletely cured areas, pores or cracks, which affects the overall quality and performance of the parts. Secondly, the high density of metal powder makes it very easy to settle in the photocuring slurry. Over time, the metal powder begins to sink, and the slurry gradually stratifies, resulting in unstable slurry properties. This instability not only affects the continuity and consistency of the printing process, but also makes it particularly difficult to print complex parts for a long time. Sedimentation problems may also cause uneven thickness of the printed layer, which in turn affects the geometric accuracy and surface quality of the parts. Ultimately, these problems may cause the printed parts to fail to meet the design requirements, limiting the scope of application of additive manufacturing technology in the metal field. Therefore, due to the poor curing characteristics and stability of photocuring slurries containing metal powders, the printing performance of existing slurries is not enough to efficiently manufacture high-performance parts. Summary of the invention
[0003] In view of the problems existing in the prior art, the present invention provides a photocurable 3D printing metal slurry and a preparation method thereof, thereby solving the technical problems in the prior art that the 3D printing slurry has poor photocuring properties, the metal powder is easy to settle, and the stability is poor.
[0004] The present invention is achieved through the following technical solutions:
[0005] A photocurable 3D printing metal slurry comprises, by weight percentage, 30% to 77% of organic monomers, 0.001% to 20% of dispersants, 0.1% to 6% of photoinitiators and 10% to 67% of composite powders; the composite powders comprise an organic shell and a metal core.
[0006] The above-mentioned method for preparing a light-cured 3D printing metal slurry is characterized by comprising the following steps:
[0007] S1: mixing an organic monomer, a diluent, a dispersant and a first amount of composite powder according to mass percentage and then performing a first ball milling to obtain a premixed solution;
[0008] S2: adding a photoinitiator and a second amount of the composite powder to the premixed liquid, and performing a second ball milling to obtain the light-cured 3D printing metal slurry;
[0009] The mass ratio of the first added amount of composite powder to the second added amount of composite powder is (20-90):(80-10).
[0010] Preferably, the first ball milling has a ball milling speed of 300 to 1600 r / min and a ball milling time of 0.1 to 10 h.
[0011] Preferably, the second ball milling has a ball milling speed of 100 to 800 r / min and a ball milling time of 0.1 to 10 h.
[0012] Preferably, the preparation process of the composite powder is: adding metal powder into an organic solution of an organic shell, stirring evenly, and spray drying to obtain the composite powder.
[0013] Preferably, the particle size of the metal powder is in the range of 0.001 to 700 μm.
[0014] Preferably, the mass percentage concentration of the organic shell solution is 1% to 40%; the mass ratio of the metal powder to the organic shell is (4 to 300):1.
[0015] Preferably, during the uniform stirring process, the stirring rate is 100 to 1600 r / min, the stirring temperature is 30 to 100° C., and the stirring time is 0.1 to 10 h.
[0016] Preferably, during the spray drying process, the temperature is -30 to 400°C, the flow rate is 50 to 2000 mL / min, and the fan frequency is 30 to 240 Hz.
[0017] The above-mentioned application of light-curing 3D printing metal slurry in additive manufacturing.
[0018] A photocurable 3D printing metal slurry is prepared by the above method.
[0019] Compared with the prior art, the present invention has the following beneficial technical effects:
[0020] The present invention discloses a photocurable 3D printing metal slurry, which contains a composite powder including an organic shell and a metal core. Compared with the original metal powder, the organic shell of the composite powder has better compatibility with the organic monomer and greater surface chemical interaction force, including van der Waals force and hydrogen bond, which promotes the dispersion of the composite powder in the organic monomer solution and provides good stability for the photocurable slurry; the refractive index of the organic matter as the shell is similar to that of the organic monomer solution, which reduces the refractive index difference between the powder and the organic monomer solution, greatly improves the curing thickness of the slurry, and obtains a stable photopolymerization slurry with good curing properties. The photocurable 3D printing metal slurry provided by the present invention has good curing properties and stability.
[0021] In addition, the present invention also discloses a method for preparing the above-mentioned light-cured 3D printing metal slurry. During the preparation process, the composite powder is added twice, and the total volume of the first added amount of composite powder and the second added amount of composite powder accounts for 10% to 67% of the total volume of the slurry; the mass ratio of the first added amount of composite powder to the second added amount of composite powder is (20 to 90): (80 to 10). Adding the composite powder twice can more effectively control the dispersion process of the powder in the slurry. The composite powder added for the first time begins to disperse during the first ball milling process, and the composite powder added for the second time can be further evenly distributed in the partially dispersed slurry. This step-by-step addition method helps to reduce the powder. agglomeration phenomenon, improving the uniformity and stability of the slurry; in addition, by controlling the proportion of the total amount of the composite powder added twice to the total volume of the slurry (10% to 67%), the viscosity of the slurry can be accurately adjusted. Viscosity is one of the key factors affecting the 3D printing process. It determines the accuracy and surface quality of the printed parts. The appropriate viscosity range helps to ensure the smooth progress of the printing process and reduce printing defects. At the same time, the mass ratio of the first added amount to the second added amount of composite powder is controlled to be (20-90): (80-10), which can balance the curing speed, curing thickness and printing accuracy of the slurry. Different mass ratios will affect the distribution and concentration of metal particles in the slurry, thereby affecting the final performance of the printed parts. The organic monomer accounts for 30% to 77% of the total volume of the slurry; the dispersant accounts for 0.001% to 20% of the total volume of the slurry; the photoinitiator accounts for 0.1% to 6% of the total volume of the slurry. Firstly, as the main component of the slurry, the organic monomer not only determines the fluidity and curing characteristics of the slurry, but also affects the mechanical properties and surface quality of the printed parts. Controlling its content within the range of 30% to 77% can ensure that the slurry has appropriate viscosity and curing speed, thereby meeting the requirements of the 3D printing process. The role of the dispersant is to promote the uniform dispersion of metal particles in the organic monomer and prevent the occurrence of agglomeration. Controlling its content within the range of 0.001% to 20% can effectively improve the slurry. The dispersion and stability of the slurry ensure the accuracy and surface finish of the printed parts. The photoinitiator is a key component in the photocuring process. It determines the curing speed and curing depth of the slurry. Controlling its content within the range of 0.1% to 6% can ensure that the slurry cures quickly under light conditions while avoiding deformation or cracking of parts caused by over-curing; accurate ingredient ratios help reduce defects in the printing process, such as bubbles, cracks, and delamination. These defects not only affect the appearance quality of the printed parts, but may also reduce their mechanical properties and service life. By optimizing the ingredient ratio, printed parts with excellent surface finish, high precision and good mechanical properties can be obtained to meet the application needs of different fields and industries.
[0022] Furthermore, the ball milling speed of the first ball milling is 300-1600 r / min, and the ball milling time is 0.1-10 h. The appropriate ball milling speed can ensure the effective collision and shear force between the ball milling medium and the slurry, thereby promoting the uniform dispersion of the composite powder in the organic monomer. Too high a ball milling speed will cause the slurry to overheat and over-shear, while too low a speed may not be sufficient to achieve effective dispersion. Sufficient ball milling time allows the powder particles to be fully dispersed in the slurry and reduce agglomeration. However, too long a ball milling time will increase the viscosity of the slurry, which is not conducive to the subsequent printing process.
[0023] Furthermore, the second ball milling speed is 100-800r / min, and the ball milling time is 0.1-10h. The second ball milling can further promote the uniform dispersion of powder particles in the slurry on the basis of the first ball milling. The appropriate ball milling speed can ensure the effective collision between the ball milling medium and the slurry, thereby facilitating the further refinement and dispersion of the powder particles. Through the second ball milling, the agglomeration phenomenon in the slurry can be further eliminated, and the stability and uniformity of the slurry can be improved, which helps to reduce fluctuations and uncertainties in the printing process, thereby improving the reliability and consistency of the printed parts. The second ball milling can also fine-tune the viscosity of the slurry to make it more suitable for the 3D printing process. The appropriate viscosity range helps to ensure the accuracy and surface quality of the printed parts.
[0024] Furthermore, the preparation process of the composite powder is: adding metal powder to an organic shell solution, stirring the reaction, and spray drying to obtain the composite powder. The method can prepare the composite powder through simple stirring reaction and spray drying steps. Compared with other complex preparation methods, such as high-temperature sintering, chemical vapor deposition, etc., the process flow of this method is simpler. The spray drying technology can quickly convert liquid into powder and has a large processing capacity, so it can significantly improve the production efficiency of the composite powder. During the stirring reaction, the metal powder can be evenly dispersed in the organic shell solution, avoiding the occurrence of agglomeration, thereby improving the dispersibility of the composite powder. The organic shell can coat the metal powder to form a protective film, which can not only improve the stability of the composite powder, but also improve its physical properties, such as hardness, wear resistance, corrosion resistance, etc.
[0025] Furthermore, the particle size range of the metal powder is 0.001 to 700 μm. The uniform and fine metal powder has better dispersion uniformity and can improve the accuracy and detail expression of the printed parts during printing. The metal powder with uniform particle size can form a flatter and smoother surface during the printing process, reducing the workload of post-processing.
[0026] Furthermore, the mass percentage concentration of the organic shell solution is 1% to 40%; the mass ratio of the metal powder to the organic shell is (4 to 300):1. The mass percentage concentration of the organic shell solution and the mass ratio of the metal powder to the organic shell directly affect the dispersion effect of the metal powder in the organic shell. The appropriate concentration and ratio can make the metal powder more evenly dispersed in the organic shell, avoid agglomeration, and thus improve the dispersibility of the composite powder. The coating effect of the organic shell on the metal powder can effectively improve the uniformity of the dispersion of the metal powder in the system. This concentration and mass ratio can effectively wrap the surface of the metal particles, and control the thickness of the surface organic shell layer to be 0.01 to 300 μm, which fully improves the stability of the system.
[0027] Furthermore, during the stirring reaction, the stirring rate is 100 to 1600 r / min, the stirring temperature is 30 to 100° C., and the stirring time is 0.1 to 10 h. This process ensures sufficient mixing and uniform dispersion of the reactants, accelerates the reaction process, and the temperature control not only accelerates the movement and collision of molecules, but also avoids the decomposition or deterioration of the product caused by high temperature, thereby improving the reaction rate and the purity of the product. In addition, the control of the reaction time ensures the full progress of the reaction and the stable generation of the product.
[0028] Furthermore, during the spray drying process, the temperature is -30 to 400°C, the flow rate is 50 to 2000 mL / min, and the fan frequency is 30 to 240 Hz. The control of these parameters allows the organic matter to dry quickly on the surface of the metal powder to form a shell with a strong bonding force. The adjustment of the flow rate and fan frequency ensures the uniform distribution of the material and efficient heat and mass transfer during the spray drying process, avoids the problems of material blockage and uneven drying, and makes the organic shell on the surface of the metal powder more uniform. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0030] Figure 1 The morphology of the composite powder obtained in Example 1 of the present invention; wherein (a) and (b) are morphology images at different scales, and (c) is a morphology image of the surface of the composite powder;
[0031] Figure 2 The longitudinal curing depth comparison results of the photocurable slurries prepared in the control group and in Examples 3 and 4;
[0032] Figure 3 The single-layer cured samples of the photocurable slurries prepared in the control group (a) and Example 3 (b) and Example 4 (c);
[0033] Figure 4 The sedimentation effect of the photocurable slurries prepared in the control group (a) and Example 3 (b) and Example 4 (c) after standing for 24 hours. DETAILED DESCRIPTION
[0034] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.
[0035] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.
[0036] Herein, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values within the range (including integers and fractions).
[0037] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”
[0038] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.
[0039] The present invention provides a method for preparing a light-cured 3D printing metal slurry, comprising the following steps:
[0040] S1: mixing an organic monomer, a diluent, a dispersant and a first amount of composite powder and then performing a first ball milling to obtain a premixed liquid;
[0041] The first ball milling has a ball milling speed of 300 to 1600 r / min and a ball milling time of 0.1 to 10 h.
[0042] In addition, the organic monomer is at least one of an acrylic group, a methacrylic group, a urethane acrylic group, an acrylamide group, a vinylthio group, an epoxy group, a silane group, an oxazolidinone group, an allyl group, a thienyl group, a furanyl group, and a vinylamino group;
[0043] The diluent is at least one of low-functionality acrylic ester monomers, low-functionality methacrylic ester monomers, vinyl monomers, ethylene oxide monomers, allyl monomers, silane monomers and alkoxy acrylic ester monomers;
[0044] The dispersant is at least one of sodium hexametaphosphate, polyvinyl pyrrolidone, silane coupling agent, oleate, sodium polyacrylate, polyethylene glycol, polyglycerol, ammonium polyacrylate and ammonium citrate.
[0045] S2: adding a photoinitiator and a second amount of composite powder to the premixed liquid, and performing a second ball milling to obtain the light-cured 3D printing metal slurry; the composite powder includes an organic shell and a metal core.
[0046] Among them, the organic monomer accounts for 30% to 77% of the total volume of the slurry; the dispersant accounts for 0.001% to 20% of the total volume of the slurry; the total volume of the first added amount of composite powder and the second added amount of composite powder accounts for 10% to 67% of the total volume of the slurry; the photoinitiator accounts for 0.1% to 6% of the total volume of the slurry.
[0047] The mass ratio of the first added amount of composite powder to the second added amount of composite powder is (20-90):(80-10).
[0048] The ball milling speed of the second ball milling is 100-800 r / min, and the ball milling time is 0.1-10 h.
[0049] The photoinitiator is at least one of 2-hydroxy-2-methyl-1-phenylpropanone, 1-hydroxycyclohexyl phenyl ketone, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, 2-dimethylamino-2-benzyl-1-[4-(4-morpholinyl)phenyl]-1-butanone, 2-hydroxy-2-methyl-1-[4-(2-hydroxyacetoxy)phenyl]-1-propanone, 2-hydroxy-2-methyl-1-phenyl-1-propanone, 1-hydroxycyclohexyl phenyl ketone and 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone.
[0050] The preparation process of the composite powder is as follows:
[0051] S1: fully dissolving a certain amount of organic shell in an organic solvent to prepare an organic shell solution with a mass percentage concentration of 1% to 40%;
[0052] S2: adding metal powder to the organic shell solution, stirring the reaction, the stirring rate is 100-1600r / min, the stirring temperature is 30-100°C, the stirring time is 0.1-10h, and then the organic solvent is evaporated by spray drying to obtain the composite powder containing the organic shell and the metal core; during the spray drying process, the temperature is -30-400°C, the flow rate is 50-2000mL / min, the fan frequency is 30-240hz, the striker interval time is 0.1-3s, and the striker execution time is 0.1-6s.
[0053] Among them, the metal powder is at least one of gold, silver, titanium, copper, tungsten, iron, tantalum, niobium, tantalum, magnesium, zinc, aluminum, platinum, copper, palladium, nickel, tin, vanadium, barium, molybdenum and alloys thereof, and the particle size range of the metal powder is 0.001 to 700 μm.
[0054] The organic shell is at least one of cellulose acetate, polystyrene, cycloolefin copolymer, polyethylene, polyvinyl alcohol, polyvinyl chloride, polycarbonate, polylactic acid, polyvinyl formal, polymethyl methacrylate, polyvinyl butyral, polyurethane, and polyamide;
[0055] The organic solvent for dissolving the organic shell is at least one of ethanol, methanol, chloroform, dichloromethane, acetone, cyclohexanone, dimethylformamide, dimethylacetamide, and tetrahydrofuran;
[0056] The mass percentage concentration of the organic shell solution is 1% to 40%, and the mass ratio of the metal powder to the organic shell is (4 to 300): 1. In the composite powder, the thickness of the surface organic shell layer is 0.01 to 300 μm.
[0057] The present invention discloses a method for preparing a slurry for photocuring 3D printing metal. First, a composite powder containing an organic shell and a spherical metal powder core is prepared by spray drying technology. Compared with the original metal powder, the organic shell of the composite powder has better compatibility with the organic monomer and greater surface chemical interaction force (such as van der Waals force or hydrogen bond), which promotes the dispersion of the composite powder in the organic monomer solution and provides good stability for the photocuring slurry. Secondly, the refractive index of the organic matter as the shell is similar to that of the organic monomer solution, which reduces the refractive index difference between the powder and the organic monomer solution, greatly improves the curing thickness of the slurry, and obtains a stable photocuring slurry with good curing characteristics. Finally, spray drying, as a process with high efficiency, strong adaptability and high degree of automation, provides a preparation method with high output, low cost and high production quality for the composite powder. In summary, the slurry preparation method provided by the present invention paves the way for photocuring 3D printing metal, broadens the range of printable metals, and enables a variety of metals to successfully manufacture components with fine features and overhanging structures at room temperature through photocuring.
[0058] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0059] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.
[0060] Example 1
[0061] A method for preparing a slurry for photocuring 3D printing titanium comprises the following steps:
[0062] S1: 7.3% titanium powder, 1.8% cellulose acetate and 90.9% dichloromethane were mixed according to mass percentage, and stirred at 60°C and 300r / min for 1h to obtain a uniform mixed solution: then, the obtained mixed solution was subjected to a spray drying process at a temperature of 140°C and a flow rate of 2000mL / min to evaporate dichloromethane to obtain a composite powder with cellulose acetate as the target shell and titanium as the core;
[0063] S2: 30% organic monomer, 67% composite powder, 2% dispersant, and 1% photoinitiator are mixed uniformly according to mass percentage to obtain a slurry. During the slurry mixing process, 70% of the composite powder and all the organic monomers, diluents, and dispersants are first added to a planetary ball mill and ball milled at a speed of 850r / min for 3h to obtain a premixed liquid. Then, the photoinitiator and the remaining composite powder are added to the premixed liquid and ball milled at a speed of 400r / min for 2h in a planetary ball mill to obtain a slurry that can be used for photocuring 3D printing of titanium. Zirconia grinding balls are used in both ball milling steps, and the ball-to-material ratio is maintained at 3.5:1.
[0064] The morphology of the composite powder in this embodiment is shown in Figure 1 ,Depend on Figure 1 It can be seen that the metal powder is wrapped by acetate fiber and has an irregular shape;
[0065] Example 2
[0066] The difference between this embodiment and embodiment 1 is that the mass ratio of titanium to acetate fiber is 40:1.
[0067] Example 3
[0068] The difference between this embodiment and embodiment 1 is that the mass ratio of titanium to acetate fiber is 22:1.
[0069] Example 4
[0070] The difference between this embodiment and embodiment 3 is that the target shell organic matter is polystyrene. 51.1% titanium powder, 2.3% polystyrene and 46.6% dichloromethane are mixed according to mass percentage to prepare a mixed solution for spray drying.
[0071] The curing properties of the photocurable 3D printed metal slurry prepared in the present invention were evaluated. Titanium and cellulose acetate (Example 3) and polystyrene (Example 4) were respectively mixed in a mass ratio of 22:1 to obtain composite powders, and the photocurable 3D printed metal slurry was prepared for photocuring tests.
[0072] The specific evaluation process is as follows:
[0073] The slurry of the photocurable 3D printed metal was dripped onto a transparent glass slide, using a resolution of 1200×800 pixels and an incident intensity of 5.7 mW / cm 2 , irradiate with a UV light source with a wavelength of 405nm for 30s. A model with a side length of 6mm and three small holes with diameters of 1000μm, 800μm, 600μm, and 400μm was selected as the curing characteristics test model. After the exposure is completed, the slide is placed in isopropanol to clean off the uncured slurry. Use a high-precision digital micrometer to measure the thickness of the single-layer cured sample; use an optical image measuring instrument to observe the single-layer samples with different exposure times, and observe the blockage of the holes under different exposure times after backlighting the image, and compare with the control group to evaluate the curing characteristics of each group, where the control group is a photocurable slurry configured with unmodified original powder. Figure 2 The longitudinal curing depth comparison results of the photocurable slurries prepared in the control group and Examples 3 and 4 are shown in the figure. It can be seen from the figure that under the same curing time, the longitudinal curing thickness of the photocurable slurry configured with the modified composite powder is larger, and the longitudinal curing thickness of the experimental group 4 is slightly larger than that of the experimental group 3. The larger curing thickness can better meet the demand for printing 3D printed parts with good printing quality and shorten the printing time.
[0074] Figure 3 The single-layer cured samples of the photocurable slurry prepared for the control group and Examples 3 and 4 show that the pores designed for the single-layer cured sample of the control group are obviously blocked, and its lateral diffusion is large, while the pores designed for the single-layer cured sample of the photocurable slurry configured with the modified composite powder are clearer and the lateral diffusion is smaller, indicating that the photocurable slurry configured with the modified composite powder has higher precision.
[0075] Furthermore, in order to evaluate the stability of the photocurable 3D printed metal slurry prepared in the present invention, titanium and cellulose acetate (Example 3) and polystyrene (Example 4) were respectively mixed in a mass ratio of 22:1 to obtain composite powders, and the photocurable 3D printed metal slurry was prepared for a static test.
[0076] The specific evaluation process is as follows:
[0077] The slurry was placed in a sealed container and allowed to stand for 24 hours. The stability of each group was evaluated by the percentage of the height of the upper layer of the slurry relative to the height of the total slurry after standing. The sedimentation rate δ of different slurries was calculated by the following formula.
[0078]
[0079] In the above formula, L is the total height of the original slurry; I is the height of the upper layer of the slurry relative to the clear liquid after 24 hours of standing. The larger the δ value, the more unstable the slurry is and the easier it is to settle.
[0080] Figure 4 3 is a sedimentation diagram of the photocurable slurry prepared in the control group and Examples 3 and 4. It can be seen from the figure that the sedimentation rates of the photocurable slurry prepared in the control group and Examples 3 and 4 are 47.6%, 2.7% and 1.6%, respectively. It can be seen that the slurry in the present invention is not prone to sedimentation and has good stability.
[0081] Example 5
[0082] A method for preparing a light-cured 3D printing metal slurry comprises the following steps:
[0083] S1: Preparation of composite powder:
[0084] A certain amount of polyethylene is fully dissolved in methanol to obtain a polyethylene methanol solution with a mass percentage concentration of 1%; copper powder with a particle size range of 100 to 500 μm is added to the polyethylene methanol solution, and stirred for 10 hours at a rate of 100 r / min and a temperature of 30°C to obtain a uniform mixed solution, and then the organic solvent is evaporated by spray drying to obtain the composite powder of the copper powder containing the polyethylene shell; during the spray drying process, the temperature is -30°C, the flow rate is 50 mL / min, the fan frequency is 240 Hz, the striker interval time is 0.1 s, and the striker execution time is 0.1 s.
[0085] The mass percentage concentration of the organic shell solution is 1%, the mass ratio of the metal powder to the organic shell is 4:1, and the thickness of the surface organic shell layer in the composite powder is 0.01 μm.
[0086] S2: mixing methacrylic acid, silane monomer, polyvinyl pyrrolidone and the first added amount of composite powder and then performing a first ball milling to prepare a premixed solution;
[0087] Wherein, the ball milling speed of the first ball milling is 300r / min, and the ball milling time is 10h.
[0088] S3: adding 2-hydroxy-2-methyl-1-phenylpropanone and a second amount of the composite powder to the premixed liquid, and performing a second ball milling to obtain the light-cured 3D printing metal slurry.
[0089] Among them, the organic monomer accounts for 30% of the total volume of the slurry; the dispersant accounts for 20% of the total volume of the slurry; the total volume of the first added amount of composite powder and the second added amount of composite powder accounts for 45% of the total volume of the slurry; the photoinitiator accounts for 5% of the total volume of the slurry.
[0090] The mass ratio of the first added amount of composite powder to the second added amount of composite powder is 20:80.
[0091] The second ball milling speed is 100 r / min, and the ball milling time is 10 h.
[0092] Example 6
[0093] A method for preparing a light-cured 3D printing metal slurry comprises the following steps:
[0094] S1: Preparation of composite powder:
[0095] A certain amount of polyvinyl formal is fully dissolved in dimethylformamide to obtain a dimethylformamide solution of polyvinyl formal with a mass percentage concentration of 40%; magnesium powder with a particle size range of 0.001 to 100 μm is added to the dimethylformamide solution of polyvinyl formal, and stirred for 0.1 h at a rate of 1600 r / min and a temperature of 100°C to obtain a uniform mixed solution, and then the organic solvent is evaporated by spray drying to obtain the composite powder containing the organic shell and the metal core; during the spray drying process, the temperature is 400°C, the flow rate is 2000 mL / min, the fan frequency is 240 Hz, the striker interval time is 3 seconds, and the striker execution time is 6 seconds.
[0096] The mass percentage concentration of the organic shell solution is 40%, and the mass ratio of the metal powder to the organic shell is 300: 1. In the composite powder, the thickness of the surface organic shell layer is 0.01-10 μm.
[0097] S2: mixing acrylic acid group, ethylene oxide monomer, sodium hexametaphosphate and the first added amount of composite powder and performing a first ball milling to obtain a premixed solution;
[0098] Wherein, the ball milling speed of the first ball milling is 1600r / min, and the ball milling time is 0.1h.
[0099] S3: adding 2-hydroxy-2-methyl-1-phenylpropanone and a second amount of composite powder to the premixed liquid, and performing a second ball milling to obtain the light-cured 3D printing metal slurry; the composite powder includes an organic shell and a metal core.
[0100] Among them, the organic monomer accounts for 55% of the total volume of the slurry, the dispersant accounts for 5% of the total volume of the slurry, the total volume of the first added amount of composite powder and the second added amount of composite powder accounts for 38% of the total volume of the slurry, and the photoinitiator accounts for 2% of the total volume of the slurry.
[0101] The mass ratio of the first added amount of composite powder to the second added amount of composite powder is 90: 10. The second ball milling speed is 800 r / min, and the ball milling time is 0.1 h.
[0102] Example 7
[0103] A method for preparing a light-cured 3D printing metal slurry comprises the following steps:
[0104] S1: Preparation of composite powder:
[0105] A certain amount of organic shell is fully dissolved in an organic solvent to obtain an organic solution with a mass percentage concentration of 20% of the organic shell; metal powder is added to the organic shell solution, stirred for 5 hours at a rate of 1000r / min and a temperature of 70°C to obtain a uniform mixed solution, and then the organic solvent is evaporated by spray drying to obtain the composite powder containing the organic shell and the metal core; during the spray drying process, the temperature is 200°C, the flow rate is 1000mL / min, the fan frequency is 100hz, the striker interval time is 2s, and the striker execution time is 5s.
[0106] The metal powder is gold, the average particle size of the metal powder is 600 μm, the organic shell is polyvinyl butyral, the organic solvent for dissolving the organic shell is tetrahydrofuran; the mass percentage concentration of the organic shell solution is 20%, and the mass ratio of the metal powder to the organic shell is 100:1. In the composite powder, the average thickness of the surface organic shell layer is 100 μm.
[0107] S2: mixing the organic monomer, the diluent, the dispersant and the first amount of the composite powder and then performing a first ball milling to obtain a premixed liquid;
[0108] Wherein, the ball milling speed of the first ball milling is 1000r / min, and the ball milling time is 5h.
[0109] In addition, the organic monomer is vinylamino, the diluent is a low-functionality acrylic ester monomer, and the dispersant is sodium hexametaphosphate.
[0110] S3: adding a photoinitiator and a second amount of composite powder to the premixed liquid, and performing a second ball milling to obtain the light-cured 3D printing metal slurry; the composite powder includes an organic shell and a metal core.
[0111] Among them, the organic monomer accounts for 55% of the total volume of the slurry; the dispersant accounts for 5% of the total volume of the slurry; the total volume of the first added amount of composite powder and the second added amount of composite powder accounts for 38% of the total volume of the slurry; the photoinitiator accounts for 2% of the total volume of the slurry.
[0112] The mass ratio of the first added amount of composite powder to the second added amount of composite powder is 50:50. The ball milling speed of the second ball milling is 500r / min, and the ball milling time is 4h. The photoinitiator is 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone.
[0113] Example 8
[0114] A method for preparing a light-cured 3D printing metal slurry comprises the following steps:
[0115] S1: Preparation of composite powder:
[0116] A certain amount of organic shell is fully dissolved in an organic solvent to obtain an organic solution with a mass percentage concentration of 30% of the organic shell; metal powder is added to the organic shell solution, stirred for 5 hours at a rate of 500r / min and a temperature of 70°C to obtain a uniform mixed solution, and then the organic solvent is evaporated by spray drying to obtain the composite powder containing the organic shell and the metal core; during the spray drying process, the temperature is 100°C, the flow rate is 500mL / min, the fan frequency is 150hz, the striker interval time is 3s, and the striker execution time is 6s.
[0117] The metal powder is iron, the average particle size of the metal powder is 300 μm, the organic shell is polyethylene, and the organic solvent for dissolving the organic shell is acetone;
[0118] The mass percentage concentration of the organic shell solution is 10%, and the mass ratio of the metal powder to the organic shell is 200: 1. In the composite powder, the thickness of the surface organic shell layer is 100 μm.
[0119] S2: mixing the organic monomer, the diluent, the dispersant and the first amount of the composite powder and then performing a first ball milling to obtain a premixed liquid;
[0120] Wherein, the ball milling speed of the first ball milling is 1000r / min, and the ball milling time is 8h.
[0121] In addition, the organic monomer is a carbamate acrylic acid group, the diluent is a low-functionality acrylic ester monomer, and the dispersant is sodium polyacrylate.
[0122] S3: adding a photoinitiator and a second amount of composite powder to the premixed liquid, and performing a second ball milling to obtain the light-cured 3D printing metal slurry; the composite powder includes an organic shell and a metal core.
[0123] Among them, the organic monomer accounts for 70% of the total volume of the slurry; the dispersant accounts for 0.5% of the total volume of the slurry; the total volume of the first added amount of composite powder and the second added amount of composite powder accounts for 24.5% of the total volume of the slurry; the photoinitiator accounts for 5% of the total volume of the slurry.
[0124] The mass ratio of the first added amount of composite powder to the second added amount of composite powder is 40:60, the ball milling speed of the second ball milling is 700r / min, the ball milling time is 9h, and the photoinitiator is 2-dimethylamino-2-benzyl-1-[4-(4-morpholinyl)phenyl]-1-butanone.
[0125] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
[0126] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A light-cured 3D printing metal slurry, characterized in that: According to the mass percentage, the raw materials include 30% to 77% of organic monomers, 0.001% to 20% of dispersants, 0.1% to 6% of photoinitiators and 10% to 67% of composite powders; the composite powders include organic shells and metal cores.
2. The method for preparing a light-cured 3D printing metal slurry as claimed in claim 1, characterized in that: The following steps are involved: S1: mixing an organic monomer, a diluent, a dispersant and a first amount of composite powder according to mass percentage and then performing a first ball milling to obtain a premixed solution; S2: adding a photoinitiator and a second amount of the composite powder to the premixed liquid, and performing a second ball milling to obtain the light-cured 3D printing metal slurry; The mass ratio of the first added amount of composite powder to the second added amount of composite powder is (20-90):(80-10).
3. The method for preparing a light-cured 3D printing metal slurry according to claim 2, characterized in that: The ball milling speed of the first ball milling is 300-1600 r / min, and the ball milling time is 0.1-10 h.
4. The method for preparing a light-cured 3D printing metal slurry according to claim 2, characterized in that: The ball milling speed of the second ball milling is 100-800 r / min, and the ball milling time is 0.1-10 h.
5. The method for preparing a light-cured 3D printing metal slurry according to claim 2, characterized in that: The preparation process of the composite powder is as follows: adding metal powder into an organic solution of an organic shell, stirring evenly, and spray drying to obtain the composite powder.
6. The method for preparing a light-cured 3D printing metal slurry according to claim 5, characterized in that: The particle size of the metal powder ranges from 0.001 to 700 μm.
7. The method for preparing a light-cured 3D printing metal slurry according to claim 5, characterized in that: The mass percentage concentration of the organic shell solution is 1% to 40%; the mass ratio of the metal powder to the organic shell is (4 to 300):
1.
8. The method for preparing a light-cured 3D printing metal slurry according to claim 5, characterized in that: During the uniform stirring process, the stirring rate is 100-1600 r / min, the stirring temperature is 30-100° C., and the stirring time is 0.1-10 h.
9. The method for preparing a light-cured 3D printing metal slurry according to claim 5, characterized in that: During the spray drying process, the temperature is -30 to 400° C., the flow rate is 50 to 2000 mL / min, and the fan frequency is 30 to 240 Hz.
10. Application of the photocurable 3D printing metal slurry in additive manufacturing as described in claim 1.
Citation Information
Patent Citations
Preparation method of composite metal for 3D printing
CN106346011A
Metal structural part and preparation method thereof
CN114406269A
Water-based 3D printing ceramic slurry and preparation method thereof
CN116553915A
Metal composite powder consisted of core-shell structure for a good laser sintering property and manufacturing method thereof
KR100889256B1
Cited By
Photocuring 3D printing metal and preparation method thereof
CN120815988A
Stainless steel metal slurry for photocuring and preparation method thereof
CN121607622A